Antibiotic Use for Genitourinary Infections in an Indonesian Hospital During COVID-19: A Retrospective Study - Nastasya Anis Abely; Fauziah Fauziah; Khamdiyah Indah Kurniasih; Fiqih Nurkholis; Ikhwan Yuda Kusuma (Fakultas Farmasi Universitas Andalas, 2024)
The management of genitourinary infections presents a growing challenge due to antimicrobial resistance, shifting regional patterns, and evolving etiologies. This study aimed to elucidate antibiotic utilization trends and patterns for genitourinary system diseases at an Indonesian teaching hospital during the COVID-19 pandemic. This retrospective, cross-sectional study analyzed antibiotic use in an Indonesian teaching hospital's inpatient department in 2021. Data on systemic antibiotics (ATC: J01) for genitourinary diseases (ICD-10: N00-N99) were extracted from electronic records. Prescription patterns were evaluated by patient characteristics, disease profiles, administration routes, and WHO AWaRe classification. Among the 47,696 hospitalized patients who received antibiotics, 1,752 were treated with J01 antibiotics for genitourinary disorders, mostly in elderly men with prostatic hyperplasia and obstructive uropathy. Cephalosporins, especially ceftriaxone (724 prescriptions) and cefazolin (294 prescriptions), were the most commonly prescribed, while amoxicillin/beta-lactamase inhibitors were the least prescribed. Parenteral administration was more common than oral, and